(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was envisaged to study the effect of cottonseed feeding on the Body Condition Score (BCS) of Murrah buffaloes. 54 lactating Murrah buffaloes were grouped into three lactation groups of early (0-3 months), mid (3-6 months) and late (>6 month), each group having 18 buffaloes which were further divided into three treatments consisting of dietary regimes of concentrate ration containing 0% cotton seed (T1- Control), concentrate ration containing 10% cottonseed (T2) and concentrate ration containing 15% cottonseed (T3). The feeding trial was performed for a period of 90 days for experimental buffaloes under different treatments of three different lactation stages. Fortnightly Body Condition Scores were recorded. While there were no significant differences in early lactation, in mid lactation there was a significant increase in T2 while T3 was comparable to T1, and in late lactation there was a significant increase in T3 while T2 was similar to control group.